BANTUL BERSAMA DALAM PENGENDALIAN KERUSAKAN TANAH - rahmah, yuyun p (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
When there is soil degradation, the productivity of the soil in supporting the life of living things will decrease. Waste product is one of the problems in Bantul Regency, for that, the Bantul Bersih Sampah 2025 (Bantul Bersama) program is an effort to manage waste to the source of waste by involving the community and stakeolder. The main target of the discussion is to find out how the conditions of soil damage are in the Bantul Regency area and the efforts to manage waste through Bantul Bersama so that it becomes a step to control soil damage. The data used is secondary data. The method used is a literature study. The damage in Kapanewon Pundong, Bantul Regency included minor damage with the limiting factors being Fraction Composition, Fill Weight, Porosity and Degree of Water Release. Bantul Bersama pursued by processing waste with the community starting from households, in groups, and management involving the Badan Usaha Milik Kalurahan (BUMKal). Good waste management as a whole is expected to reduce the impact of environmental damage and the potential for economic utilization.